2022
DOI: 10.3390/jcm11092295
|View full text |Cite
|
Sign up to set email alerts
|

Gardnerella vaginalis in Recurrent Urinary Tract Infection Is Associated with Dysbiosis of the Bladder Microbiome

Abstract: Recent studies on the urine microbiome have highlighted the importance of the gut–vagina–bladder axis in recurrent urinary tract infection (rUTI). In particular, the role of Gardnerella as a covert pathogen that activates E. coli in animal experiments has been reported. Herein, we conducted a human bladder microbiome study to investigate the effect of Gardnerella on rUTI. Urine 16S ribosomal RNA gene sequencing via transurethral catheterization was conducted in the normal control group (NC) (n = 18) and rUTI g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…UTI caused by G. vaginalis in children was first described in 2020, 2 and this is the third reported case; therefore, few studies have discussed the importance of or indications for UTI treatment caused by G. vaginalis in children. A study that performed meta‐16S rRNA gene analysis on urine samples from adult UTI patients reported G. vaginalis detection in 18.8% of cases, 3 indicating that G. vaginalis ‐positive UTI cases outnumber those encountered in clinical settings. However, because G. vaginalis requires special culture media, including chocolate agar medium, it can easily be missed, unless it is suspected by careful observation of Gram staining, as in this case.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…UTI caused by G. vaginalis in children was first described in 2020, 2 and this is the third reported case; therefore, few studies have discussed the importance of or indications for UTI treatment caused by G. vaginalis in children. A study that performed meta‐16S rRNA gene analysis on urine samples from adult UTI patients reported G. vaginalis detection in 18.8% of cases, 3 indicating that G. vaginalis ‐positive UTI cases outnumber those encountered in clinical settings. However, because G. vaginalis requires special culture media, including chocolate agar medium, it can easily be missed, unless it is suspected by careful observation of Gram staining, as in this case.…”
Section: Figurementioning
confidence: 99%
“…As G. vaginalis ‐positive UTI in adults is often a mixed infection, 3 only E. coli or E. faecalis detected in the same urine sample are usually treated. Therefore, even if we can detect G. vaginalis , we tend to recognize it as contamination and exclude it from treatment targets.…”
Section: Figurementioning
confidence: 99%
“…Another hypothesis, the gut–vaginal–bladder axis, is that quorum sensing and poly-infection exist between the strain that enters the bladder from the gut and causes UTI and the strain that enters the vagina and enters the bladder causing UTI, with Gardnerella vaginalis playing an important role ( Figure 1 ). Kim and Yoo et al have recently found that three different sub-urotypes in the bladder through a study of 78 patients with recurrent cystitis [ 22 ]. The three sub-urotypes are: (1) recurrent UTI (rUTI) could occur in an environment in which UPEC is dominant; (2) rUTI could occur in an environment in which Gardnerella vaginalis is dominant; and (3) cystitis could occur in an environment in which Lactobacillus is dominant [ 22 ].…”
Section: Axis Crosstalkmentioning
confidence: 99%
“…Kim and Yoo et al have recently found that three different sub-urotypes in the bladder through a study of 78 patients with recurrent cystitis [ 22 ]. The three sub-urotypes are: (1) recurrent UTI (rUTI) could occur in an environment in which UPEC is dominant; (2) rUTI could occur in an environment in which Gardnerella vaginalis is dominant; and (3) cystitis could occur in an environment in which Lactobacillus is dominant [ 22 ].…”
Section: Axis Crosstalkmentioning
confidence: 99%
“…Yoo et al[19] conducted a human bladder microbiome study to investigate the effect of Gardnerella on recurrent UTI (rUTI). The Gardnerella-dominant or Lactobacillus-dominant groups expressed rUTI with symptoms in the presence of risk factors such as the degree of Gardnerella proliferation or causative agents of bacterial vaginosis.Depending on other risk factors, the presence of Gardnerella in the urine is considered to be related to rUTI.The majority of UM studies have focused on adult subjects, and pediatric reports are scarce.…”
mentioning
confidence: 99%